Gender pay gap in Spanish local governments - Guillamón, María D.; Cuadrado-Ballesteros, Beatriz; Ríos, Ana M. (Cities, 2024)
Despite the fact that more and more women are gaining access to important policy-making positions, they do not usually receive salaries as high as those of men. Furthermore, women attaining top-tier positions frequently have fewer possibilities of exercising any significant authority, providing a potential explanation for gender pay disparities. The previous literature on the public sector pay gap has mainly focused on public sector workers, but we have not found any empirical analyses of the pay gap for mayors. In this context, our paper aims to analyse whether there is a gender pay gap among local mayors. We also examine whether this pay gap is affected by the percentage of women in the local council, not solely by the mayor's gender. We use a sample of 140 Spanish municipalities for 2014–2022. After estimating with GMM, our results show that female mayors receive lower salaries than their male counterparts, confirming a pay gap. Nevertheless, we find that this gap is narrower when the proportion of women in the council increases, which is a powerful argument for demanding the presence of more women in public institutions. •Female mayors receive lower salaries than their male counterparts, confirming a pay gap.•Pay differences between male and female mayors decrease as the proportion of female councillors increases.•Increasing the proportion of women in public organisations would help to reduce the current gender pay gap.•Actions and legislation should be implemented to further promote women’s participation in public administrations.